The impact of ethanol and iso-butanol blends on gaseous and particulate emissions from two passenger cars equipped with spray-guided and wall-guided direct injection SI (spark ignition) engines. (15th March 2015) - Karavalakis, Georgios; Short, Daniel; Vu, Diep; Russell, Robert L.; Asa-Awuku, Akua; Jung, Heejung; Johnson, Kent C.; Durbin, Thomas D.
Abstract: We examined the effects of different ethanol and iso-butanol blends on the gaseous and particulate emissions from two passenger cars equipped with spark ignition direct injection engines and with one spray-guided and one wall-guided configuration. Both vehicles were tested over triplicate FTP (Federal Test Procedure) and UC (Unified Cycles) using a chassis dynamometer. Emissions of THC (total hydrocarbons), NMHC (non-methane hydrocarbons), and CO (carbon monoxide) reduced with increasing oxygen content in the blend for some of the vehicle/fuel combinations, whereas NO x (nitrogen oxide) emissions did not show strong fuel effects. Formaldehyde and acetaldehyde were the main carbonyls in the exhaust, with the higher ethanol blends showing higher acetaldehyde emissions during the cold-start. For butyraldehyde emissions, both vehicles showed some increases with different butanol blends when compared to ethanol blends, but not for all cases. The higher ethanol and butanol blends showed reductions in PM (particulate mass), number, and soot mass emissions. Particulate emissions were significantly affected by the fuel injection design, with the wall-guided vehicle producing higher mass and number emissions compared to the spray-guided vehicle. Particle size was influenced by ethanol and iso-butanol content, with higher alcohol blends showing lower accumulation mode particles than the baseline fuel. Highlights: THC, NMHC, CO, CO2, and CH4 emissions reduced with higher alcohol blends. Butyraldehyde emissions increased with higher butanol blends relative to ethanol fuels. Wall-guided fueling showed significantly higher PM than spray-guided fueling. PM and particle number emissions trended lower with higher ethanol and butanol blends. Higher oxygen/lower aromatic content blends reduced accumulation mode particles.